5PSQ-011 Complications of drug containing parenteral nutrition: a cohort study - Rodríguez Ramallo, H; Báez Gutiérrez, N; Ciudad Gutiérrez, P; Pérez Blanco, JL; Mejias Trueba, M; Santos Ramos, B (European journal of hospital pharmacy. Science and practice, 2020)
Background and importanceParenteral nutrition (PN) is an intravenous formulation composed of a wide variety of nutrients. Adding drugs to PN have certain advantages although associated drawbacks have been described, such as the risk of instability and incompatibility with macro or micronutrients.Aim and objectivesTo evaluate if the addition of certain drugs to PN was associated with a higher incidence of PN complications.Material and methodsThis retrospective observational cohort study included hospitalised patients treated with personalised PN from July 2018 to July 2019. Paediatric patients and those who received PN for >3 days were excluded. Variables collected: age, sex, cause of hospitalisation, PN administration route, presence of drugs in PN, duration of PN treatment and PN complications. PN were classified as drug containing PN if somatostatin, ranitidine, insulin or metoclopramide were added.Descriptive and correlation analyses between PN complications and the rest of the studied variables were carried out. Statistical analysis was performed by OR and logistic regression using IBM SPSS Statistic 24 package.ResultsA total of 185 patients were included, 56.2% men, median age 60.5 years (18–89 years): 26 patients were excluded. The causes of hospitalisation were neoplasia in 44.86%, digestive pathologies in 34.05%, infections in 11.35% and other pathologies in 9.73%.The PN administration route was a central catheter in 76.9% of patients and a peripheral catheter in the remaining patients: 43.24% (n=80) of patients suffered plasmatic electrolyte alterations during PN treatment and 11.89% (n=22) suffered catheter infections. No statistically significant differences were observed for age, sex, cause of hospitalisation, catheter type, incidence of metabolic complications or electrolyte alterations (p>0.1). A larger number of catheter infections occurred in patients receiving drug containing PN (OR 2.69 (1.08–6.67)).Median duration of PN treatment was 12 days (3–138). Treatment duration was longer for patients receiving drug containing PN (21.03 vs 14.44 days, p<0.05). Duration of PN treatment was correlated with the onset of catheter infections (p<0.0001).Conclusion and relevanceNo correlation was found between the addition of drugs to PN and most studied complications. Patients who received drug containing PN had a higher risk of catheter infections. The longer duration of treatment with drug containing PN may be the cause of the increased incidence of infections.References and/or acknowledgements1. Trissel L. Trissel’s stability of compounded formulations, 6th edn. APA, 2018.No conflict of interest.